Learning Transformation in the Digital Era: Development of Virtual Reality-Based Learning Media to Increase Student Efficiency and Creativity - Wulandari, Sholihah Ayu; Rosyady, Ahmad Fahriyannur; Sucipto, Adi; Wulandari, Sekar Ayu (Angkasa: Jurnal Ilmiah Bidang Teknologi, 2024)
During the COVID-19 pandemic, its impact was felt in Indonesia's education world, especially when learning was online or offline. Every lecturer in educational institutions is expected to provide the latest innovations to create an effective learning process. In the post-COVID-19 pandemic era, the digitalization of education in Indonesia is experiencing rapid growth, and advances in information technology are an opportunity to increase creativity in learning media. One proposed method is the development of Virtual Reality-based learning media, which can support the quality of the teaching and learning process. The development of Virtual Reality-based learning media includes intelligent systems for the Informatics Engineering Study Program, and Agro-Industry Plantation Management for the Agro-Industry Management Study Program, especially at Campus 4 PSDKU Sidoarjo – Politeknik Negeri Jember. The results of the development of Virtual Reality-based learning media are in the form of visualization illustrations of students' understanding of the Intelligent Systems and Plantation Agro-Industry Management courses. This technology is expected to facilitate student participation with learning resources more efficiently than conventional learning media which only allows one-way communication. Based on the results of evaluations via questionnaires to students, it is known that learning efficiency reaches 82% when using Virtual Reality-based learning media.